Impact of Implementation of Destructive Concepts in Public Administration - Irina V. MINAKOVA; Tatyana N. BUKREEVA; Olga I. SOLODUKHINA; Daniil I. RASPOPIN (Communications of International Proceedings, 2020)
The purpose of the study is to generalize and systematize Russian management practice based on false scientific theories. The authors have analyzed such destructive influence processes as orientation of organizational policy towards post-industrialism, inefficiency of monetization of the economy, application of liberal theory, which led to reduction of state regulation of socio-economic processes and excessive openness of the national economy. It was identified that these concepts and ideas were brought to Russian state practice from the outside (in particular, they were recommended by the International Monetary Fund (the IMF). The authors have revealed that introduction of these false concepts weakened Russia’s national potential.
Keywords: Management Practice; Post-Industrialism; Monetization Of The Economy; Liberal Theory; State Regulation Of Economy.